EKSPLORASI INFLASI DAN PENANAMAN MODAL ASING (PMA) TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) - Herman Sjahruddin; Abd. Rachim Syah; Munandar Makmur; Muh. Agung Permana; Ahmad Miswar; Hamry Ashary (LP2M Universitas Bina Bangsa, 2024)
This study aims to analyze the impact of inflation and foreign investment on gross regional domestic product in Indonesian provinces. This research uses a quantitative approach that intends to explore high and low GDP in Indonesian provinces. The population in this study is all provinces in Indonesia amounting to 38, sampling techniques using purposive sampling with a total sample of 30 provinces that meet the criteria. The analysis used is Panel Data Regression with the help of eviews 12 software. The results of the analysis show that inflation has a real impact on the increase in gross regional domestic product, then foreign investment also proves that it can significantly affect the increase in gross regonal domestic product